Standoff [large type] - Bradley, Patricia, 1945- (Bradley, Patricia, 1945- Natchez Trace Park Rangers, 2020)
"The Natchez Trace National Parkway stretches 444 miles from Nashville to Natchez, the oldest town on the Mississippi River. It's the perfect road for a relaxed pleasure drive. Unfortunately for park ranger Luke Fereday, lately it's being used to move drugs. Sent to Natchez to infiltrate the organization at the center of the drug ring, Luke arrives too late to a stakeout and discovers the body of his friend, park ranger John Danvers.John's daughter Brooke is determined to investigate her father's murder, but things are more complicated than they first appear, and Brooke soon finds herself the target of a killer who will do anything to silence her. Luke will have his hands full keeping her safe. But who's going to keep him safe when he realizes he's falling--hard--for the daughter of the man he failed to save?"--Provided by publisher.